2019
DOI: 10.1097/bpo.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Growth Friendly Surgery and Serial Cast Correction in the Treatment of Early-onset Scoliosis for Patients With Prader-Willi Syndrome

Abstract: Level IV-therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Severe curves are casted until the child is old enough to undergo surgery for an expandable spine implant (5-8 years of age) ( Figure 4). Oore et al reported the only published series of serial casting for children with PWS, noting a reduction of curve size in their ten patients, from 45° to 37° [40]. We reviewed our results from 34 children with PWS with more than 24 months' follow-up after their initial spine cast.…”
Section: Serial Spinal Castingmentioning
confidence: 97%
See 3 more Smart Citations
“…Severe curves are casted until the child is old enough to undergo surgery for an expandable spine implant (5-8 years of age) ( Figure 4). Oore et al reported the only published series of serial casting for children with PWS, noting a reduction of curve size in their ten patients, from 45° to 37° [40]. We reviewed our results from 34 children with PWS with more than 24 months' follow-up after their initial spine cast.…”
Section: Serial Spinal Castingmentioning
confidence: 97%
“…In addition, up to 62% of patients with PWS have low bone mineral density and other musculoskeletal manifestations [11,[42][43][44][45][46]. The combination of the PJK/DJK and bone weakness leads to a rate of hardware pull out/failure/rod fracture between 17% and 31% [9,40,41,47,48]. The consequences can be catastrophic [49].…”
Section: Bracingmentioning
confidence: 99%
See 2 more Smart Citations